Nostra Aetate and Encountering Buddhism - Feldmeier, Peter (Buddhist Christian studies, 2020)
Peter Feldmeier points to Vatican II's Nostra Aetate as a key turning point for Catholicism's posture toward the religious other. Here we find that God works in and through these religions and is intimately involved in the souls of all peoples in the context of their religions. While retaining the traditional perspective of holding Christ as the absolute revelation of God, Nostra Aetate also provides the foundation for seeing religious others as bearers of insight unique to their own religion. Feldmeier then points to advancements beyond Nostra Aetate, particularly with the leadership of Pope John Paul II, to greater appreciation of postmodernity in the theological academy, and the development of the discipline of comparative theology. Collectively, they have allowed the seeds of Nostra Aetate to germinate and flourish. Using his own life as an example, Feldmeier shows how being influenced by Buddhism provides additional perspectives for rethinking or enriching Christian faith. Specifically, he shows how Buddhist sensitivities allow one to hear Jesus's teachings in a deeper way, reconsider sin more holistically, rethink how to better imitate Christ, and see how Buddhist meditation strategies could facilitate Christian transformation, even traditionally understood. Feldmeier shows that post-Vatican II Catholicism has had a complex and not wholly receptive relationship with the religious other, particularly Buddhism. Paradoxically, some of these stumbling blocks have provided impetus to a deepening engagement with Buddhism.